Does A Longer Waiting Period After Neoadjuvant Radio-chemotherapy Improve the Oncological Prognosis of Rectal Cancer?: Three Years' Follow-up Results of the Greccar-6 Randomized Multicenter Trial. Issue 5 (November 2019) - Lefèvre, Jérémie H.; Mineur, Laurent; Cachanado, Marine; Denost, Quentin; Rouanet, Philippe; de Chaisemartin, Cécile; Meunier, Bernard; Mehrdad, Jafari; Cotte, Eddy; Desrame, Jérome; Karoui, Mehdi; Benoist, Stéphane; et al.
Abstract : Objective: The aim of this study was to report the 3-year survival results of the GRECCAR-6 trial. Summary Background Data: Current data on the effect of an extended interval between radiochemotherapy (RCT) and resection for rectal cancer on the rate of complete pathological response (pCR = ypT0N0) is controversial. Furthermore, its effect on oncological outcomes is unknown. Methods: The GRECCAR-6 trial was a phase III, multicenter, randomized, open-label, parallel-group, controlled trial. Patients with cT3/T4 or TxN+ tumors of the mid or lower rectum who had received RCT (45–50 Gy with 5-fluorouracil or capecitabine) were included and randomized into a 7- or 11-week waiting period. Primary endpoint was the pCR rate. Secondary endpoints were 3-year overall (OS), disease-free survival (DFS), and recurrence rates. Results: A total of 265 patients from 24 participating centers were enrolled. A total of 253 patients underwent a mesorectal excision. Overall pCR rate was 17% (43/253). Mean follow-up from surgical resection was 32 ± 8 months. Twenty-four deaths occurred with an 89% OS at 3 years. DFS was 68.7% at 3 years (75 recurrences). Three-year local and distant recurrences were 7.9% and 23.8%, respectively. The randomization group had no impact on the 3-year OS ( P = 0.8868) or DFS ( P = 0.9409). Distant ( P = 0.7432) and local ( P = 0.3944) recurrences were also not influenced by the waiting period. DFS was independently influenced by 3 factors: circumferential radial margin (CRM) ⩽1 mm [hazard ratio (HR) = 2.03; 95% confidence interval (CI), 1.17–3.51], ypT3-T4 (HR = 2.69; 95% CI, 1.19–6.08) and positive lymph nodes (HR = 3.62; 95% CI, 1.89–6.91). Conclusion: Extending the waiting period by 4 weeks following RCT has no influence on the oncological outcomes of T3/T4 rectal cancers. Abstract : Supplemental Digital Content is available in the text